Comparison of the injection‐site experience of the starting doses with semaglutide and dulaglutide: A randomized, double‐blind trial in healthy subjects. Issue 6 (18th March 2021) - Snitker, Søren; Andersen, Andreas; Berg, Birgitte; van Marle, Sjoerd; Sparre, Thomas
Abstract: This double‐blind, randomized, single‐site, crossover trial compared the injection‐site experience with the starting doses of semaglutide and dulaglutide. Healthy subjects (aged 18–75 years; body mass index ≥ 25 kg/m 2 ; n = 104) were randomized 1:1, using a pregenerated list, to semaglutide 0.25 mg as the first injection and dulaglutide 0.75 mg as the second injection or vice versa; each was administered using their proprietary pen‐injectors, according to instructions for use. The primary endpoint was intensity of injection‐site pain, measured using a visual analogue scale (VAS; 0 mm = no pain, 100 mm = unbearable pain). Exploratory endpoints included intensity category, duration and quality of injection‐site pain, and comparative assessment of injection‐site pain with the two injections. The point estimate of the VAS score for injection‐site pain intensity was 11.5 mm with dulaglutide versus 5.6 mm with semaglutide; mean (95% confidence interval) estimated treatment difference 5.9 (3.6; 8.2) mm; p < .0001. Other endpoints corroborated a less painful injection experience with semaglutide versus dulaglutide. Safety was consistent with reported data for the drugs. In conclusion, the injection‐site experience with semaglutide was rated as less painful than that with dulaglutide.